Usefulness of composite indices in the assessment of joint involvement in systemic lupus erythematosus patients: correlation with ultrasonographic score. (March 2019) - Ceccarelli, F; Perricone, C; Cipriano, E; Massaro, L; Natalucci, F; Spinelli, F R; Alessandri, C; Valesini, G; Conti, F
Specific indices are not available to evaluate systemic lupus erythematosus (SLE) joint involvement; indeed, the application of indices validated for rheumatoid arthritis has been suggested. We evaluated the usefulness of organ specific composite indices, i.e. the Disease Activity Score on 28 joints (DAS28), Simplified Disease Activity Index (SDAI), Clinical Disease Activity Index (CDAI), and the ratio of swollen to tender joints (STR), to assess SLE joint activity by analyzing the correlation between these indices and ultrasonography (US) inflammatory status. We evaluated SLE patients with arthralgia and/or arthritis: the above-mentioned indices were calculated and the SLE Disease Activity Index 2000 (SLEDAI-2k) was applied to assess global disease activity. US of I–V metacarpophalangeal, I–V proximal interphalangeal, wrist, and knee bilateral was performed. Synovial effusion/hypertrophy and power Doppler findings were scored according to a semi-quantitative scale (0–3) to obtain an inflammatory total score (0–216). One hundred and six patients (M/F 7/99, median age 49.5 years (IQR 17.0), median disease duration 8.5 years (IQR 17.0)) were enrolled. We identified a positive correlation between US score and DAS28-CRP ( r = 0.3, p = 0.007), STR ( r = 0.42, p = 0.0005), SDAI ( r = 0.33, p = 0.02), CDAI ( r = 0.29, p = 0.03); US score reflected different levels of clinimetric joint activity. In conclusion, we suggest the ability of composite indices in detecting SLE joint inflammation and their possible real-life use.